Ultrasonographicpotencial in detection of Acute Appendicitis - V. N. Piskunov; V. D. Zavadovskaya; N. G. Zavyalova (Бюллетень сибирской медицины, 2009)
On the grounds of ultrasonography of 275 patients with suspected Acute Appendicitis (AA) the diagnosis was confirmed in 63 (22,9%) cases, it was true-positive results; in 3 (1,1%) cases of non-confirmed AA ultrasound findings were regarded as false-positive results. True-negative results of examination were obtained in 194 cases (70,5%) and false-negative results — in 15 cases (5,5%). The presence of rarevascularity of interior wall and clear visualization of vessels in mesentery of vermiform appendix is typical for congestive appendicitis. When phlegmonous appendicitis there are numerous vascular branches in interior wall blood stream of appendix: they make a picture of color «crown» in horizontal section and color «stripe» in longitudinal section. Gangrenous appendicitis is attached to few color spots in those parts of appendix wall which are not destroyed yet. Vascular pattern in adjacent intestinal loops predominates over vascular pattern of vermiform appendix. In case of empyema vermiform appendix vascular pattern in the wall is detected only in mesentery area. Vascular pattern of appendix is not detected in cases of appendicular infiltrate and periappendicular abscess unlike vascular pattern of adjacent intestinal loops which is rather intensified. The sensitivity of ultrasonography in AA detection was 80,7%, specificity — 98,4%, and accuracy — 93,4%. High index of diagnostic effectiveness of the method was obtained because of adoption of combining B-mode with both Colour Doppler and Power Doppler methods.